2016
DOI: 10.1002/mgg3.261
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of c.422_423InsT, a novel mutation of the HNF1A gene in a patient with diabetes

Abstract: Background HNF1A gene regulates liver‐specific genes, and genes that have a role in glucose metabolism, transport, and secretion of insulin. HNF1A gene mutations are frequently associated with type 2 diabetes. HNF1A protein has three domains: the dimerization domain, the DNA‐binding domain, and the trans‐activation domain. Some mutations in the dimerization or DNA‐binding domains have no influence on the normal allele, while others have dominant negative effects. The I27L, A98V, and S487N polymorphisms are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…S11h ). Previous studies have shown that frameshift mutations in the DNA-binding domain can cause dominant-negative effects 41 .…”
Section: Resultsmentioning
confidence: 99%
“…S11h ). Previous studies have shown that frameshift mutations in the DNA-binding domain can cause dominant-negative effects 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the hESC heterozygous line harboring a frameshift mutation in the DNA-binding domain and causing a premature stop codon presented a stronger bias towards a-cell fate. Previous studies in MODY3 patients have shown that frameshift mutations in the DNA-binding domain cause dominantnegative effects affecting the DNA binding capacity of the normal HNF1A (43).…”
Section: Hnf1a R200q Homozygous Mutation Is Pathogenic and Causes A Dmentioning
confidence: 98%
“…The GCK variant p.Gly80Ala was located within the glucokinase ATP binding site, where Gly80 residue plays a role in its formation, although not directly binding ATP (29,30). The novel missense variant p.Ala15Asp is located within the HNF1A N-terminal dimerization domain (31), and p.Cys55Tyr -within a highly conserved HNF4A zinc-nger DNA binding domain (32). Another novel missense variant, p.Glu339Val, is also expected to have a negative effect on gene function, as it occurs within the GCK gene mutational hot spot.…”
Section: Identi Cation Of Mody Causative Variantsmentioning
confidence: 99%